A phosphoryl radical-initiated Atherton–Todd-type reaction under open air. Issue 9 (6th January 2020) - Ou, Yingcong; Huang, Yuanting; He, Zhenlin; Yu, Guodian; Huo, Yanping; Li, Xianwei; Gao, Yang; Chen, Qian
Abstract : A phosphoryl radical-initiated Atherton–Todd-type reaction enables the phosphorylation of alcohols, phenols, and amines under mild reaction conditions. Abstract : A phosphoryl radical-initiated Atherton–Todd-type reaction using air as the radical initiator and CHCl3 as the halogenating reagent for the phosphorylation of alcohols, phenols, and amines has been developed. This novel transformation provides a highly efficient route to important phosphinates, phosphinic amides, and phosphoramidates in up to 99% yield with a broad substrate scope under very mild conditions (48 examples).